Modified solid industrial waste as potential catalyst in pyrolysis - Kamil, Faten Hameed (2016)
Disposal of industrial waste has become a significant environmental issue. Increasing environmental awareness draws attention to find alternative uses to industrial solid waste. In this work, industrial wastes such as aluminum dross from aluminium recycling process, molten slag from steel manufacturing process and spent oil based mud from petroleum well drilling were treated by physical and chemical methods for potential use in the pyrolysis applications. The industrial wastes were evaluated using state of the arts analysis techniques before and after physical and chemical treatments. The results showed the physical method which representing calcination did not affect much on the properties of the materials like surface area, pore volume, acidity and thermal stability. While the chemical methods were prone to give better properties. Therefore, acid washing method by using hydrochloric acid was chosen as good and economical procedure to improve the activity of the waste material by removing impurities and increasing surface area and acidity of the waste materials for potential catalysts. The surface area and acidity of aluminum dross and spent oil based mud was increased from 0.96 to 68.24 m2/g and from 315 to 748 μmol/g, from 0.58 to 0.61 m2/g and from 496 to 1255 μmol/g, respectively. Even though the surface area of molten slag was reduced from 3.4 to 0.85 m2/g, the acidity was increased from 159 to 1224 μmol/g. The performance of these catalysts was assessed by utilizing them in pyrolysis of waste cooking oil in a fractional system as a feedstock at reaction temperature of 390-420°C with fixed catalyst loading of 5% . The results showed an increase in the yield of the biofuel product produced from the pyrolysis process. Al dross and molten slag were observed to be the best potential catalyst as showed by the gas chromatography analysis. The yield of bio-oil using Al dross as catalyst was 16.43% with 3.2% alkane and 2.5% alkene and the bio-oil using molten slag as catalyst was 14.9% with yield of 18.5% alkanes and 11.76% alkenes and good selectivity in the biofuel range namely C7 to C17. In conclusion, industrial solid waste after a few modifications, have a potential to be a catalyst in pyrolysis waste cooking oil although they were not showed very significant features in the characterization. All waste materials have a potential as catalysts showing good yield in the catalytic pyrolysis compared to thermal cracking. The product distribution and selectivity obtained from catalytic pyrolysis of waste cooking oil using Al dross and molten slag gave the best performance compared to spent oil based mud-modified catalysts.